Borate-Water-Based 3D-Slime Interface Quasi-Solid Electrolytes for Li-ion Batteries - Shiratori, Yosuke (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.